ANALISIS TINDAK TUTUR NOVEL HAFALAN SHALAT DELISA KARYA TERE LIYE MENGGUNAKAN PENDEKATAN PRAGMATIK - Nanang Ma Ruf (Universitas Wijaya Kusuma Surabaya, 2022)
This study discusses the analysis of speech acts in the novel entitled Memorization of Prayer Delisa by Tere Liye. The purpose of this study is (1) to describe the form of locutionary speech acts (2) to describe the form of illocutionary speech acts (3) to describe the form of perlocutionary speech acts. This research is expected to be useful for: (1) for students, the results of this study can be used as reference material for future research with related discussions. (2) the results of this study can provide additional knowledge and insight for readers about the pragmatic point of view contained in the novel, especially the novel Memorization of Prayer Delisa by Tere Liye. This type of research is descriptive qualitative. The source of the data taken by the researcher is a novel entitled Memories of Delisa Prayers by Tere Liye. The method used is reading and taking notes. The instruments used are (1) the researcher as the first instrument, (2) the Memorable Prayer Delisa novel by Tere Liye. Data collection uses the method of reading and taking notes if the dialogue results in speechlessness. The results of the research are as follows. First, the researcher found the types of speech acts consisting of (1) locutionary speech acts, (2) illocutionary speech acts, (3) perlocutionary speech acts. These types of speech acts contain communication functions including (1) Imperative locutionary speech acts, (2) Declarative locutionary speech acts, (3) Interrogative locutionary speech acts, (4) Arrestive illocutionary speech acts, (5) Directive illocutionary speech acts, (6) Commissive illocutionary speech acts, (7) Expressive illocutionary speech acts, (8) illocutionary declaration speech acts.